Reflections from the field : how coaching made us better teachers - DeMeulenaere, Eric J.; Cann, Colette N.; Malone, Chad R.; McDermott, James E. (Emerald Publishing Limited : Information Age Publishing, 2013)
The coaching metaphor first entered the educational literature over twenty-five year ago when Ted Sizer urged classroom teachers to model the pedagogical relationship between coaches and athletes. Yet, since then, educators have rarely drawn direct lessons from the athletic arena for their practice... until now. DeMeulenaere, Cann, Malone and McDermott, in this groundbreaking analysis, explore the implications of athletic coaching for improved pedagogy. They offer concrete lessons and suggestions for best practices in the classroom.